Preparation method and application of zinc oxide / copper indium sulfide composite material

By growing CuInS2 nanofilm on ZnO nanorod array and forming a ZnO/CuInS2 nanoarray structure, the problem of poor light absorption performance of ZnO/CuInS2 composite materials in the prior art is solved, and wide spectrum absorption and material stability are achieved Improved performance, suitable for solar cells and photoelectric sensors and other fields.

CN119181643APending Publication Date: 2024-12-24JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311727522.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing ZnO/CuInS2 composite materials have poor light absorption performance in the visible light range, are difficult to apply in the wide spectrum field, and the material stability is insufficient.

Method used

The ZnO nanorod array was prepared by vapor deposition and thermal annealing, and CuInS2 nanofilm was grown on it by hydrothermal method to form a ZnO/CuInS2 nanoarray structure, enhancing light absorption and transmission capabilities.

Benefits of technology

It realizes wide spectrum light absorption in the fields of solar cells and photoelectric sensors, improves the stability of the material and interface bonding intensity, expands the absorption range of visible light, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181643A_ABST
    Figure CN119181643A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a zinc oxide / copper indium sulfide composite material, and the preparation method comprises the following steps: growing a ZnO seed layer on a substrate, then transferring into a tubular furnace, adding a Zn source, and reacting at 450-700 DEG C for 0.5-1.5 h to obtain a ZnO nanorod; and placing the ZnO nanorod in a precursor solution containing a copper source, an indium source and a sulfur source, reacting at 140-180 DEG C for 10-14 hours, and after the reaction, carrying out annealing treatment to crystallize the ZnO nanorod to obtain the ZnO / CuInS2 composite material. The invention provides a ZnO / CuInS2 composite material with wide spectrum absorption, which realizes efficient absorption in a solar wide spectrum range. The structure has the characteristics of high interface bonding strength, good stability and wide wavelength response, and has wide application prospects in the fields of solar cells, photocatalysis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoelectric materials, and in particular to a preparation method and application of a zinc oxide / indium copper sulfide composite material. Background Art

[0002] Photoelectric materials are a type of material that has the property of converting light energy into electrical energy or electrical energy into light energy. These materials play an important role in solar cells, photodetectors, LED lights, optical fiber communications, etc., and improving the efficiency of photoelectric conversion and broadening the absorption spectrum range have become the focus of research.

[0003] ZnO is a wide bandgap semiconductor with a bandgap of about 3.37 eV, and has a strong absorption capacity for ultraviolet light. This means that ZnO can absorb the ultraviolet part of the solar spectrum, but has weak absorption of visible light and near-infrared light. 2 It is a narrow bandgap semiconductor with a bandgap of about 1.5 eV, which means it can absorb a wide spectrum from visible light to the near-infrared region. 2 When combined to form a heterojunction, the interface of the two materials can promote the effective separation of photogenerated carriers (electrons and holes), which not only enhances the material's absorption of light, but also improves the separation efficiency of photogenerated carriers, which is crucial for photoelectric conversion and photocatalytic applications. 2 The composite material is mainly used in the ultraviolet band. Due to the limitation of ZnO material, its light absorption performance in the visible light range is poor, making it difficult to use in the visible light range.

[0004] The literature "CuInS 2 Preparation and Performance Study of Quantum Dot Sensitized ZnO-based Photoanode" (Wuhan University of Technology, 2020, Xia Donglin) ZnO nanorods were prepared by a two-step method, and CuInS was deposited on ZnO nanorods by continuous ion layer adsorption reaction. 2 Quantum dots, preparation of CuInS 2 Quantum dot-sensitized ZnO-based photoanode materials. The prepared ZnO / CuInS 2 After the wavelength of light reaches 400 nanometers, the light absorption rate begins to decrease. 2 The absorption spectrum of the composite material is still narrow. The literature "Preparation of ZnO-based composite materials and study of their photocatalytic properties" (Northwest University, 2021, Liu Congquan) prepared ZnO samples by combining precipitation method and heat treatment, and prepared CuInS by in-situ growth under stirring reflux conditions combined with hot injection method. 2 / ZnO. From its light absorption curve, it can be seen that different CuInS 2 CuInS loading2 / ZnO composite materials showed a significant decrease in light absorption at a wavelength of 400nm. 2 / ZnO composite materials are not suitable for application in the visible light band, so a ZnO / CuInS with a wide light absorption range and strong material stability is studied. 2 Composite materials are a difficult problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above prior art, the purpose of the present invention is to provide a preparation method and application of zinc oxide / indium sulfide copper composite material. The present invention adopts vapor deposition and thermal annealing to prepare ZnO nanorod arrays, whose high surface area and excellent conductivity properties help to enhance light absorption and transmission. CuInS 2 Nanofilm, prepared ZnO / CuInS 2 The nanoarray structure has high efficiency in wide-spectrum light absorption and can make full use of a wide range of solar light. This structure can be applied to solar cells, photoelectric sensors and other photoelectric conversion fields that require wide-spectrum absorption.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A first aspect of the present invention provides a method for preparing a zinc oxide / indium copper sulfide composite material, comprising the following steps:

[0008] A method for preparing a zinc oxide / indium copper sulfide composite material, characterized in that it comprises the following steps:

[0009] (1) growing a ZnO seed layer on the substrate, then transferring it into a tube furnace, adding a Zn source, and reacting at 450-700°C for 0.5-1.5h to obtain ZnO nanorods;

[0010] (2) placing the ZnO nanorods in a precursor solution containing a copper source, an indium source, and a sulfur source, reacting at 140-180°C for 10-14 hours, and annealing after the reaction to crystallize them to obtain ZnO / CuInS 2 Composite materials.

[0011] Preferably, the precursor solution is composed of CuCl 2 、InCl 3 and Na 2 S aqueous solution; in the precursor solution, Cu 2+ The concentration of In is 10-100mM; 3+ The concentration of S is 10-100mM. 2- The concentration is 10-100mM.

[0012] Preferably, in step (2), the annealing temperature is 100-140° C. and the time is 5-7 h.

[0013] Preferably, in step (1), the specific method for growing the ZnO seed layer on the ITO glass is:

[0014] The ITO glass is cleaned with acetone, ethanol and deionized water in sequence, and then spin-coated with an ethanol solution containing zinc acetate, and reacted at 250-350° C. for 10-20 minutes to form a ZnO seed layer.

[0015] Preferably, the concentration of zinc acetate is 5 ml / L.

[0016] The second aspect of the present invention provides a zinc oxide / indium sulfide copper composite material prepared by the above preparation method.

[0017] The third aspect of the present invention provides the use of the zinc oxide / indium copper sulfide composite material in the field of photoelectric conversion with wide spectrum absorption.

[0018] Beneficial effects of the present invention:

[0019] 1. The present invention provides a ZnO / CuInS with wide spectrum absorption 2 The composite material achieves efficient absorption over a wide spectrum of the sun; the construction of this structure has high interface bonding strength, good stability and wide wavelength response characteristics, and has broad application prospects in solar cells, photocatalysis and other fields.

[0020] 2. The present invention provides a fast, simple, low-cost, large-scale production of CuInS 2 / ZnO structure preparation method.

[0021] 3. ZnO nanorods of different sizes can be obtained by controlling the reaction time and temperature. The diameter of the ZnO nanorods can be adjusted from 20nm to 50nm; the length of the ZnO nanorods can be adjusted from 0.5μm to 2μm. ZnO rods of appropriate size can provide more light absorption interfaces and paths, so that light can be absorbed more effectively in the material. For example, when the reaction time is 0.5h, the diameter and length of the prepared nanorods are 20nm and 0.5μm, respectively, and the corresponding light absorption performance is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : ZnO / CuInS prepared in Example 1 2 SEM images of the composite materials;

[0023] Figure 2 : ZnO / CuInS prepared in Example 1 2 EDX analysis of composite materials;

[0024] Figure 3 : ZnO nanorods and ZnO / CuInS prepared in Example 1 2 XRD spectra of the composite materials;

[0025] Figure 4 :ZnO / CuInS 2 XPS spectra of composite materials;

[0026] Figure 5 : ZnO / CuInS prepared in Example 1 2 Composite material, ZnO nanorods and CuInS prepared in Comparative Example 1 2 The absorption spectrum of . DETAILED DESCRIPTION

[0027] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0028] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0029] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0030] Example 1: ZnO / CuInS 2 Preparation of composite materials:

[0031] (1) Preparation of ZnO seed layer: First, the ITO glass was cut into a size of 1 cm × 3 cm, and then cleaned with acetone, ethanol and deionized water for 15 min in sequence to remove impurities and contaminants on the surface, and then spin-coated with an ethanol solution of zinc acetate (the concentration of zinc acetate was 5 ml / L), and finally reacted at a temperature of 300 ° C for 10 min to form a ZnO seed layer;

[0032] (2) Preparation of ZnO nanorods: The ZnO seed layer prepared above was placed in a tubular furnace, Zn powder was used as a Zn source, and the reaction was carried out at 500° C. for 0.5 h to obtain ZnO nanorods; the diameter and length of the ZnO nanorods were 20 nm and 0.5 μm, respectively.

[0033] (3) Preparation of precursor solution: The precursor solution consists of CuCl 2 、InCl 3 and Na 2 S aqueous solution; in the precursor solution, Cu 2+The concentration of In 3+ The concentration of S is 50mM. 2- The concentration is 50mM;

[0034] (4) The obtained ZnO nanorods were placed in 25 ml of precursor solution and CuInS was prepared by hydrothermal method. 2 The reaction temperature is 160℃, the growth time is 12h, and then thermal annealing is performed. The annealing temperature is 120℃ and the time is 6h to crystallize ZnO / CuInS 2 Composite materials.

[0035] Example 2: ZnO / CuInS 2 Preparation of composite materials:

[0036] (1) Preparation of ZnO seed layer: First, the ITO glass was cut into a size of 1 cm × 3 cm, and then cleaned with acetone, ethanol and deionized water for 15 min in sequence to remove impurities and contaminants on the surface, and then spin-coated with an ethanol solution of zinc acetate (the concentration of zinc acetate was 5 ml / L), and finally reacted at a temperature of 300 ° C for 10 min to form a ZnO seed layer;

[0037] (2) Preparation of ZnO nanorods: The ZnO seed layer prepared above was placed in a tube furnace, Zn powder was used as a Zn source, and the reaction was carried out at 500° C. for 1.25 h to obtain ZnO nanorods; the diameter and length of the ZnO nanorods were 50 nm and 0.5 μm, respectively;

[0038] (3) Preparation of precursor solution: The precursor solution consists of CuCl 2 、InCl 3 and Na 2 S aqueous solution; in the precursor solution, Cu 2+ The concentration of In 3+ The concentration of S is 50mM. 2- The concentration is 50mM;

[0039] (4) The obtained ZnO nanorods were placed in 25 ml of precursor solution and CuInS was prepared by hydrothermal method. 2 The reaction temperature is 160℃, the growth time is 12h, and then thermal annealing is performed. The annealing temperature is 120℃ and the time is 6h to crystallize ZnO / CuInS 2 Composite materials.

[0040] Example 3: ZnO / CuInS 2 Preparation of composite materials:

[0041] (1) Preparation of ZnO seed layer: First, the ITO glass was cut into a size of 1 cm × 3 cm, and then cleaned with acetone, ethanol and deionized water for 15 min in sequence to remove impurities and contaminants on the surface, and then spin-coated with an ethanol solution of zinc acetate (the concentration of zinc acetate was 5 ml / L), and finally reacted at a temperature of 300 ° C for 10 min to form a ZnO seed layer;

[0042] (2) Preparation of ZnO nanorods: The ZnO seed layer prepared above was placed in a tube furnace, Zn powder was used as a Zn source, and the reaction was carried out at 700° C. for 1.5 h to obtain ZnO nanorods; the diameter and length of the ZnO nanorods were 50 nm and 2 μm, respectively;

[0043] (3) Preparation of precursor solution: The precursor solution consists of CuCl 2 、InCl 3 and Na 2 S aqueous solution; in the precursor solution, Cu 2+ The concentration of In 3+ The concentration of S is 50mM. 2- The concentration is 50mM;

[0044] (4) The obtained ZnO nanorods were placed in 25 ml of precursor solution and CuInS was prepared by hydrothermal method. 2 The reaction temperature is 160℃, the growth time is 12h, and then thermal annealing is performed. The annealing temperature is 120℃ and the time is 6h to crystallize ZnO / CuInS 2 Composite materials.

[0045] Comparative Example 1: CuInS 2 Preparation of materials

[0046] CuCl 2 、InCl 3 and Na 2 S aqueous solution together, stirring to make it fully mixed, so that Cu 2+ The concentration of In 3+ The concentration of S is 50mM. 2- The concentration of CuInS was 50 mM; the reaction was carried out at 160 ° C for 12 h, and then a thermal annealing treatment was carried out at a temperature of 120 ° C for 6 h to crystallize the CuInS 2 Material.

[0047] Test Example 1:

[0048] The ZnO / CuInS prepared in Example 1 2 Composite materials performance characterization:

[0049] 1. Scanning electron microscopy (SEM) analysis:

[0050] The ZnO / CuInS prepared in Example 1 was analyzed by scanning electron microscopy (ZEISS Sigma 300). 2 Microstructure and structure of the composite material. ZnO / CuInS 2 The composite nanorod arrays exhibited rod-like and high aspect ratio structural features under SEM.

[0051] 2.EDX analysis:

[0052] The energy dispersive X-ray spectrometer (EDX) equipped with a scanning electron microscope was used to analyze the ZnO / CuInS prepared in Example 1. 2 In addition to Zn and O, Cu, In and S elements were also detected in the composite materials. Figure 2 ), indicating that CuInS 2 Successfully deposited on the surface of ZnO samples.

[0053] 3.XRD spectrum analysis:

[0054] The ZnO nanorods and ZnO / CuInS prepared in Example 1 were analyzed by X-ray diffractometer (XRD-D8 Venture). 2 XRD spectra of the composite materials ( Figure 3 ), by comparing with the standard card, it can be found that the three characteristic peaks (100), (002) and (101) are consistent with the wurtzite structure of ZnO (JCPDS No.36-1451). The peaks at 27.9°, 46.2° and 55.1° in the spectrum of the composite sample correspond to CuInS 2 Three characteristic diffraction peaks of the (112), (204) and (312) crystal planes of the chalcopyrite structure (JCPDS: No. 27-0159).

[0055] 4.XPS test:

[0056] In order to further confirm the chemical state and elemental composition of the sample, the ZnO / CuInS 2 The composites were studied by XPS. Figure 4 The XPS full spectrum shows the presence of five elements: Zn, O, Cu, In and S. The two peaks at 1022eV and 1045.1eV are Zn 2p 3 / 2 and Zn 2p 1 / 2 The signal peaks at 532.1eV and 531.3eV of O 1s correspond to the lattice oxygen O 2- and oxygen vacancies, the binding energy of the two peaks is Cu 2p 3 / 2 and Cu 2p 1 / 2The difference between the two energies is 19.8 eV, which is consistent with the reported Cu + The two peaks at 444.9 eV and 452.5 eV are split by In 3d, which is consistent with the In 3+ On the other hand, the two split peaks in the S2p high-resolution spectrum are 3 / 2 and S2p 1 / 2 , corresponding to S 2- , further confirming that the composite material sample is ZnO / CuInS 2 .

[0057] Test Example 2:

[0058] Light absorption performance test:

[0059] The ZnO / CuInS prepared in Example 1 was measured by UV-visible absorption spectrometer (Shimadzu UV-3600i Plus). 2 Composite material, ZnO nanorods prepared in Example 1 and CuInS prepared in Comparative Example 1 2 The light absorption performance of the Figure 5 ), with ZnO and CuInS 2 Compared with ZnO / CuInS 2 The nanoarray has the best absorption performance in the wavelength range of 300nm-800nm; compared with ZnO, ZnO / CuInS 2 Effectively expands the absorption range of visible light.

[0060] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a zinc oxide / indium copper sulfide composite material, characterized in that: The following steps are involved: (1) growing a ZnO seed layer on the substrate, then transferring it into a tube furnace, adding a Zn source, and reacting at 450-700°C for 0.5-1.5h to obtain ZnO nanorods; (2) placing the ZnO nanorods in a precursor solution containing a copper source, an indium source and a sulfur source, reacting at 140-180° C. for 10-14 hours, and annealing after the reaction to crystallize them to obtain a ZnO / CuInS2 composite material.

2. The preparation method according to claim 1, characterized in that: In the precursor solution: Cu 2+ The concentration of In 3+ The concentration of S is 10-100mM. 2- The concentration is 10-100mM.

3. The preparation method according to claim 1, characterized in that: In step (2), the annealing temperature is 100-140°C and the time is 5-7h.

4. The preparation method according to claim 1, characterized in that: In step (1), the specific method for growing a ZnO seed layer on the ITO glass is: The ITO glass is cleaned with acetone, ethanol and deionized water in sequence, and then spin-coated with an ethanol solution containing zinc acetate, and reacted at 250-350° C. for 10-20 minutes to form a ZnO seed layer.

5. The preparation method according to claim 4, characterized in that: The concentration of zinc acetate is 5 ml / L.

6. A zinc oxide / indium sulfide copper composite material prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the zinc oxide / indium copper sulfide composite material according to claim 6 in the field of photoelectric conversion with wide spectrum absorption.